POPULATION ASPECT IN ORGANIC AGRICULTURE - S. K. Temirbekova; J. D. Van Mansvelt (Труды по прикладной ботанике, генетике и селекции)
Article is devoted studying of variability of cultivated plants varieties characters within their populations. The structure of ecoelements in populations of several wheat varieties of different geographical origin, with different ecological features has been studied in one climatic zone. Variability of populations phenotypical structure was investigated with use of different effects: various dates of crops sawing, temperature factors, an light mode. Various variants of variability of the investigated characters have been revealed. Results of research can be used for improvement of cultivated plants varieties quality.